The Optimum Replacement of Fine Recycled Concrete Aggregate on the Mechanical Properties of the Concrete - Sheikh Khalid, Faisal; Zaki, Zahir; N A A, Guntor; A J L, Meng Siang (International Journal of Integrated Engineering, 2020)
This paper will review the optimum replacement of the fine natural aggregate (FNA) by the fine recycled concrete aggregate (FRCA) that are gathered from the construction and demolition waste. This will cover about the properties of the FRCA itself, the mechanical properties of the concrete incorporating with FRCA and the most suitable replacement of the FRCA in the concrete mixing design. The use of FRCA now a days is getting popular among researchers due to the environmental factor in mining industries to get the coarse aggregate and depletion of the river and shore sand for the fine aggregate which are able to affect the geological structure of the surrounding area. That is why it is vital to get a better understanding about the recycled concrete aggregate (RCA) so that it could be used and provide a clear relevant fact for the industries to start review the existing regulation and consider the use of RCA in the concrete making.